(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
The birth cohort pattern of risk for breast cancer among European women is remarkably similar to that observed among women in the United States and Canada. A sharp decrease in risk for women born after World War II is particularly intriguing, and warrants further epidemiological investigation in order to identify etiologic factors potentially responsible for the unexpected and unexplained declining risk.